Direct Ink Writing of Materials for Electronics-Related Applications: A Mini Review - Hou, Zhenzhong; Lu, Hai; Li, Ying; Yang, Laixia; Gao, Yang (Frontiers in Materials, 2021)
Recently, the fabrication of electronics-related components via DIW has attracted much attention. Compared to the conventionally fabricated electronic components, DIW-printed ones have more complicated structures, higher accuracy, improved efficiency, and even enhanced performances that arise from well-designed architectures. The direct material deposition characteristic of the DIW process enables it to print on a variety of flat substrates, even a conformal one, well suiting them to applications such as wearable devices and on-chip integrations. Here, recent developments in DIW printing of emerging components for electronics-related applications are briefly reviewed, including electrodes, electronic circuits, and functional components. The printing techniques, processes, ink materials, advantages, and properties of DIW-printed architectures are discussed. Finally, the challenges and outlooks on the manufacture of 3D structured electronic devices by DIW are outlined, pointing out future designs and developments of DIW technology for electronics-related applications. The combination of DIW and electronic devices will help to improve the quality of human life and promote the development of science and society.